Identification and analysis of factors affecting the maturity of knowledge-based companies in the food industry with the approach of the fourth-generation industry - Ali Mohaghar; Fatemeh Saghafi; Mohammad Hasan Maleki; Daryamehr Keshani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The current research seeks to identify and prioritize factors affecting the maturity of knowledge-based companies in the food industry, focusing on the approach of the fourth-generation industry.Methodology: The current research is applied in terms of orientation and it is a quantitative study from the point of view of methodology. The theoretical population of the research is the specialists of organizational maturity and the fourth-generation industry in the food industry. Sampling in this research was done based on the expertise of experts in the field of research. In this research, the fuzzy Delphi method was used to screen the factors and Copras and Mabac techniques were used to prioritize the screened factors. Interviews with focus groups were also used to provide practical suggestions.Findings: The present research was carried out in several stages. In the first step, factors affecting the maturity of knowledge-based companies in the food industry were extracted through literature review and interviews with experts. To screen the factors, expert questionnaires were distributed among the experts, and the experts expressed their opinions about each of the factors in the form of a five-degree fuzzy spectrum. 10 factors had a favorable defuzzified number and were selected for final prioritization. Screened factors were evaluated by distributing priority questionnaires and Copras and Mabac techniques. The experts expressed their opinions in the form of a spectrum of 10 point on four indicators. The priority factors were: governance of data-driven decision-making culture, the use of new learning methods in the organization, the use of cloud platforms in the organization, the use of smart machines and equipment in the company, and innovation policies in the organization.Originality/Value: Practical research proposals were developed based on the most important factors. Some suggestions were: the use of data-driven technologies such as business intelligence and big data to strengthen data-driven decision-making, the use of a hybrid approach in training and the application of new technologies in the field of training such as Metaverse, the use of Internet of Things and blockchain technologies to automate and intelligentize processes and finally Moving towards an open innovation policy.